Efficency Analysis of Rice Production and Farmers' Income in Sengah Temila District Landak Regency - Pudaka, Deo Leko; Rusdarti, Rusdarti; Prasetyo, P. Eko (Journal of Economic Education, 2018)
The low production of rice in Sengah Temila District of Landak Regency makes farmers’ income low. The purpose of this research was to analyze production, efficiency (technical, price and economy) and farmer income. The approach used in this research was quantitative approach. The production analysis used Cobb-Douglas’s production function with multiple linear regressions. Technical efficiency analysis used frontier production function with Stochastic Frontier Analysis (SFA). Allocative efficiency analysis used comparative analysis of marginal product value and input price. Economic efficiency analysis used the combination of technical efficiency and allocative efficiency. The income analysis used the difference between revenue and cost. The results showed that the average production of rice in Sengah Temila District Landak Regency was quite good with production of 5.819 kg/ha. The factors that affect the production level significantly ware the land size, seeds, pesticides and labors while the fertilizer factor had no significant effect because of quantity of fertilizer was less than needed. Land size was dominant factor that affect the production level. Technical efficiency was not yet efficient but it was nearly efficient with coefficient 0.96. Inefficiency of technical becuase of quantity of fertilizer was less than needed and over capacity of land. Based on allocative efficiency, the rice farming was far from efficient due to the high price of production factors, especially fertilizer and labor with coefficient 19.24. Economic efficiency was not efficient with coefficient of 18.38. Farmer’ income was Rp1,385,900.00 per household per month. Farmer' income was lower than the regional minimum wage (UMR) of Landak Regency in 2017 which was Rp2,000,920.00.